Cyfrowy dostęp do informacji i danych o funkcjonowaniu państwa a prawo do informacji jako prawo człowieka - Żyła, Łukasz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The right to information and the concept of information itself are nowadays the subject of interest of many scientific disciplines dealing with human rights, constitutional law, administrative law, but also (in the context of the development of information society) information technology. In this article, subjecting to a critical analysis of the existing literature in this area, I intend to put forward a thesis on the significant influence of the forms and modes of digital access to information on the functioning of the state on the realisation of the right to information as a human right, and to make a general analysis of the provisions regulating this issue.
Keywords: access to information; open data; digital government; digital information; right to information; polish legislation